Cystic meningioma of the brain - Long, Jiang (Nervenheilkunde, 2024)
Meningiomas with a cystic component are quite rare and account for 1.7–7.3 % of all intracranial meningiomas. The incidence of cystic meningioma in adults is 2–4 % of all meningiomas. Women have a higher incidence rate in comparison to men. Between 2014 and 2019, at the State Institution Romodanov Neurosurgery Institute of the National Academy of Medical Sciences of Ukraine, we collected data for a database of cystic meningioma cases. The data included preoperative imaging, surgery notes, and pathology reports. Over the course of 6 years, 1408 meningioma cases have been observed, and 1326 of those instances have undergone surgical treatment for intracranial meningioma. 73 (5.5 %) cases of cyst-associated meningiomas have been analyzed: 26 (2.0 %) of true cysts (primary), 47 (3.5 %) cases of pseudocysts (secondary). Nauta type IV was the most common cyst type accounting for 52.1 %, whereas atypical (27.4 %) and anaplastic (17.8 %) meningioma types were the most common histological subtypes. All patients were monitored for 24 months; only 73 patients had access to long-term monitoring, which lasted for an average of 49 months (range 36–96 months). The majority of atypical (2.7 %) and anaplastic (5.5 %) types of pseudocystic meningioma relapsed after radical tumor surgery removal. The preoperative diagnosis needs to be integrated with the examination performance, the surgical treatment is selected based on the Nauta classification, and most of the surgical operations can result in the complete resection of the tumor.
Keywords: Histopathology; surgery; MRI; Nauta classification; aseptic meningitis syndrome; intracranial hypotension syndrome